Tin oxide as an electron transport layer in perovskite solar cells: Advances and challenges - Wali, Qamar; Aamir, Muhammad; Ejaz Khan, Muhammad; Jose, Rajan; Fan, Wei; Yang, Shengyuan (Elsevier Ltd, 2024)
Perovskite solar cells (PSCs) have appeared as a growing photovoltaic technology owing to their unprecedented performance compared to the market leader, silicon solar cells. The high efficiency (η) of 26 % within a decade brings hope for the photovoltaic community. However, their operational stability remains a critical issue and hinders their commercialization. Charge transport layers play a key role in the stability and overall performance of PSCs. While TiO2 is the most common and successfully employed electron transport layer (ETL), it is neither a very efficient charge extractor at the interfaces nor stable under UV illumination. Alternatively, another promising ETL, such as SnO2, has recently emerged, producing remarkable performance in PSCs. The outstanding performance in SnO2-based ETL is owing to its extraordinary properties, such as its better band alignment with common perovskite material and higher mobility while being processable at low temperatures (∼150 °C). The best reported result with η = 25.4 % for SnO2 ETL has been achieved so far, comparable to that of the most employed ETL-based TiO2 (η = 26 %). In this review, recent progresses in SnO2-based PSCs with η greater than 20 % and stability (>1000 h) are summarized together with a discussion on associated challenges and opportunities, with an emphasis on the road ahead for commercialization.